Low proficiency learners in synchronous computer-assisted and face-to-face interactions - Tam, S.S.; Kan, N.H.; Ng, L.L. (Turkish Online Journal Educational Tech-Tojet, 2010)
This experimental study offers empirical evidence of the effect of the computer-mediated environment on the linguistic output of low proficiency learners. The subjects were 32 female undergraduates with high and low proficiency in ESL. A within-subject repeated measures concurrent nested QUAN-qual (Creswell, 2003) mixed methods approach was used. Interactions between the subjects in mixed ability dyads in face-to-face (F2F) and synchronous computer-assisted (SCA) environments provide the data. The unit of analysis was negotiation of meaning (Varonis & Gass, 1985) which is the key construct that is claimed to promote second language acquisition (SLA). The evidence indicates that opportunities for SLA for low proficiency learners are enhanced with the occurrences of negotiation of meaning in both SCA and F2F environments. In particular, the SCA allowed for varied syntactic and semantic modifications which provided ample opportunities for low proficiency learners to negotiate for comprehensible input and to notice form.